Young childless women with breast cancer in the UK: a qualitative study of their fertility‐related experiences, options, and the information given by health professionals. Issue 1 (29th August 2013) - Corney, Roslyn Heather; Swinglehurst, Amica Jane
Abstract Objective A proportion of young women diagnosed with breast cancer are childless. Fertility can be impaired by treatment, and women may have to wait for a number of years before pregnancy is advised. The aim of this qualitative study was to investigate in detail the fertility‐related experiences of young childless women with breast cancer, including the information they received, the fertility preservation options given, and the dilemmas they faced. Method Interviews were conducted with 19 childless women aged below 45 with first episode breast cancer diagnosed at least 6 months before. They were recruited by contacting the breast cancer charities and were asked to tell their story, with an emphasis on fertility issues. Transcripts were analyzed using the thematic method developed by Braun and Clarke. Results The amount of information given to women from health professionals varied considerably. Only half were given the opportunity to pursue assisted reproductive techniques prior to chemotherapy. Most women were worried about what the future might hold, including their fertility, the impact of pregnancy on recurrence, and the health of the child. They were generally given little information or support on these issues. Conclusions Young women should be given more detailed information about fertility issues shortly after diagnosis, after chemotherapy, and during follow‐up appointments. More holistic care should include emotional support to enable them to make decisions regarding their fertility options and planning for the future. Copyright © 2013 John Wiley & Sons, Ltd.